Morbidity and mortality of children aged 2–59 months admitted in the Tanzania Lake Zone’s public hospitals: a cross-sectional study - Lugangira, Kristina (BMC Res Notes, 2017)
BACKGROUND: There is a growing concern about child mortality especially in developing countries. The Government of Tanzania and non-governmental organizations are fighting against diseases like malaria, anaemia, diarrhoea and pneumonia that contribute extensively to child mortality. This was a hospital-based, retrospective cohort study involving 1130 under-fives (excluding neonates) being either discharged from or died in public hospitals of the Lake Zone in Tanzania. We extracted information on symptoms and signs at admission, major diagnoses and causes of death from the medical records. We applied binary logistic regression models to assess risk factors associated with in-patient under-five death. RESULTS: The major leading morbidities include malaria (49%), anemia (37%), diarrhea (27%), pneumonia (22%) and severe acute malnutrition (21%). We found the case fatality of 74 deaths per 1000 under-five admissions. Major underlying causes of deaths were severe anaemia, severe malaria and severe pneumonia. Factors associated with in-patient death were female sex (AOR 1.7; 95% CI 1.0, 2.8) and the odds significantly decreased with increasing level of maternal education. CONCLUSIONS: Malaria remains a leading cause of admissions in hospitals among under-fives. Although the case fatality among children aged between 2 and 59 months admitted in hospitals in Lake Zone is decreasing, efforts are needed to address major causes of deaths (severe anaemia, severe malaria and severe pneumonia).